MECHANISMS OF REGULATION FOR EDUCATION IN BRASIL: CONTRIBUTIONS FOR A DEBATE - Chirinea, Andreia Melanda (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This article seeks to discuss how the external evaluations subsidize the regulation in Brazilian State education as well as evidencing the mechanisms engendered that subordinate the education to the market. Therefore it discusses from a general view the process of regulation in Brazilian basic education, evidencing the accountability conceptions and regulation. The paper supported itself in the review of literature as a way of adding the main concepts that characterize the theoretical framework found in Afonso (2001) and Barroso (2005) its greatest exponents. Finally from the discussions carried out in this article it is possible to infer that we are under the aegis of an evaluative State and that either to the Basic Education Development Index (Ideb) or the Basic Education Assessment System (Saeb) are heralds of the State regulation for Brazilian public education.
Keywords: External evaluation; Regulation; Ideb